Intimasi Pertemanan ditinjau dari Self-Disclosure pada Mahasiswa Jurusan Kebidanan Universitas Prima Indonesia - Sherly Sherly; Sri Hartini; Yulinda S. Manurung (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to know the relationship between the intimate friendship with self-disclosure. The hypothesis in this study is there is a positive relationship between self-disclosure with intimate friendship, in assumption that the higher self-disclosure, the higher intimate friendship is and the lower self-disclosure, then the lower intimate friendship itself. The subjects that used in this study are the midwifery students at the Prima Indonesia University, in which the population consists of 103 students. Data obtained from the scale to measure self-disclosure and intimate friendship. The calculation of the datas began by doing a test prerequisite analysis (the test of assumptions) that consists of a test of normality and a test of linearity. The data analysis in this study uses the Product Moment Correlation with SPSS 25 for Windows. The results of analysis showed the correlation coefficient at 0.731 of the significance 0.000 (p < 0.05). This shows there is a positive relationship between self-disclosure with intimate friendship. The results of this study indicate that the variable of intimate friendship can be predicted by self-disclosure at 53.5 percent and 46.5 percent of the rest are influenced by other factors which not examined in this study. Based on the results of this study, the hypothesis of there is a positive relationship between self-disclosure with intimate friendship is acceptable.